Der Kaiser und sein Gott Das Christentum im Denken und in der Religionspolitik Konstantins des Großen - Girardet, Klaus M. (Millennium-Studien / Millennium Studies, 2010)
In his reconstruction of the process and motivation of Constantine`s adoption of Christianity, the author proposes a number of new individual aspects. He commences with an analysis of theearliest testimonials bythe Emperor himself after his conversion, his massive moral and material support for the Christian clergy and ecclesiastic communities, andConstantine`srole as the first ruler of all Christendom up to his death in 337. Finally, it is shown that the Emperor wanted to suppress non-Christian religions and make Christianity the sole religion of the Empire and all humanity.